2013
DOI: 10.1007/s11046-013-9618-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Black Fungal Biofilms Occurring at Domestic Water Taps (I): Compositional Analysis Using Tag-Encoded FLX Amplicon Pyrosequencing

Abstract: Mass growth of dark fungal biofilms on water taps and associated habitats was observed in various German drinking water distribution systems recently. Customers of affected drinking water systems are anxious about potential and unknown health risks. These environments are known to harbour a fungal flora also comprising a variety of fungal opportunists that are well known to cause superficial mycoses in humans (Exophiala equina, Exophiala lecanii-corni) but are not known to establish dark biofilms so far. To ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 53 publications
0
23
0
2
Order By: Relevance
“…Examinations of bathwater and sludge in drainpipes that are warmed daily to over 42°C have identified several species of this medically important genus [20]. Recently, mass growth of dark fungal biofilms on water taps and associated habitats was observed in various German drinking water distribution systems [21,22]. Here, E .…”
Section: Introductionmentioning
confidence: 99%
“…Examinations of bathwater and sludge in drainpipes that are warmed daily to over 42°C have identified several species of this medically important genus [20]. Recently, mass growth of dark fungal biofilms on water taps and associated habitats was observed in various German drinking water distribution systems [21,22]. Here, E .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the presence of fungi in groundwater associated with degradation of plant debris is limited or reported less often. On the other hand, oligotrophic conditions support growth of melanised fungi, such as Aureobasidium melanogenum , high diversity of Exophiala species and Rhinocladiella similis (Table 1) [9,11,19,23,26,66,67]. These species were regularly reported from different European countries from both ground- and tap water, but were rarely reported in a relation to surface water, pointing toward groundwater as the main source of contamination of tap water with these opportunistic pathogenic fungi (Table 1) [19].…”
Section: Fungi and Water—background Informationmentioning
confidence: 99%
“…Fungal biofilms were fully formed within 48 h from the beginning of an experiment mimicking real conditions in tap systems [132]. The presence of fungi in in vivo biofilms from tap systems in private homes, hospitals or industrial network was confirmed for opportunistic and pathogenic species from the genera Aspergillus , Candida , Exophiala , Fusarium , Malassezia , Ochroconis , Penicillium , Phialophora , Phoma and Rhinocladiella [23,26,27,31,133,134]. Once established, biofilms are difficult to be fully removed from the pipe system, which on the long-term leads to altered taste and odour of water, production of allergenic or irritating compounds, and mycotoxins with an effect on human health (Figure 1) [2,21].…”
Section: Fungi and Water—background Informationmentioning
confidence: 99%
See 2 more Smart Citations